2020
DOI: 10.18823/asiatefl.2020.17.4.9.1294
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phonemic Awareness Instructions on L2 Listening Comprehension: A Meta-Analysis

Abstract: This study examines the effect of phonemic awareness instruction on listening comprehension ability in learning English as a second language or foreign language (L2). The searching procedures were carried out using Publish or Perish with discreetly selected keywords. Eight studies with 13 samples published between 2000 and 2020 were obtained. Hedges' g was calculated, leveraging Comprehensive Meta-Analysis (CMA) software. The overall effect size of phonemic awareness instruction on listening skills was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Yopp (1992) defined phonemic awareness as the understanding that sequences of speech sounds coins spoken words and syllables. For example, phonemic awareness is to understand that the sounds /r/ /a/ /t/ form the word 'rat' and the word 'car' consists of the sounds /k/ /a/ /r/ (Choe et al, 2020). Once children acquire phonemic awareness skill, they can address the phonemes and manipulate them in spoken words (Adams, 1994;Griffith & Olson, 1992;Liberman et al, 1974).…”
Section: Phonemic Awareness and Learning To Readmentioning
confidence: 99%
“…Yopp (1992) defined phonemic awareness as the understanding that sequences of speech sounds coins spoken words and syllables. For example, phonemic awareness is to understand that the sounds /r/ /a/ /t/ form the word 'rat' and the word 'car' consists of the sounds /k/ /a/ /r/ (Choe et al, 2020). Once children acquire phonemic awareness skill, they can address the phonemes and manipulate them in spoken words (Adams, 1994;Griffith & Olson, 1992;Liberman et al, 1974).…”
Section: Phonemic Awareness and Learning To Readmentioning
confidence: 99%
“…Among those components, phonological awareness and reading comprehension strategies may have a longer term benefit for reading than other approaches [ 46 , 47 ]. The explicit teaching of phonological awareness and phonics benefited spelling, expressive vocabulary [ 48 ], reading [ 48 , 49 ], and listening [ 50 ] amongst ELL. Explicitly supporting children to understand the link between phoneme-grapheme correspondence knowledge and the reading context is also an effective intervention strategy for ELL struggling to learn to read [ 51 ].…”
Section: English Language Learnersmentioning
confidence: 99%
“…Phonemic awareness education should be linked with listening training in EFL situations since learners have difficulties discerning foreign phonemes (Lee, 2021). A meta-analysis of the effect of phonemic awareness on listening comprehension in English as a second or foreign language (ESL/ EFL) explored eight articles (Choe et al, 2020). The result revealed that it is especially beneficial for beginner or younger learners.…”
Section: Phonemic Awarenessmentioning
confidence: 99%
“…Despite the fact that young learners are thought to acquire a foreign language with less effort than adults (Snow, 2014), they were chosen to see if they encounter difficulties discriminating new consonants. This is because young learners benefit most from segmental feature teachings (Choe et al, 2020), and it necessitates a more urgent exploration of their perceptions. Brown (1988) and Catford (1987) proposed a ranking of segmental differences in terms of Functional Load Principle in English pronunciation.…”
Section: Speech Learning Modelmentioning
confidence: 99%